Pemanfaatan Lumpur Limbah Tahu di Dusun Sugihmanik sebagai Upaya Konservasi Air untuk Mewujudkan Green Econom - Ramadan, Bimastyaji Surya; Sarminingsih, Anik; Elawati, Nunung Eni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Sugihmanik Village in Grobogan Regency, Central Java, has many people who work as tofu producers. However, this village is experiencing an environmental management crisis, one of which is the management of sludge resulting from the liquid waste processing process at their wastewater treatment plant (IPAL). One of the proposed solutions is the use of tofu waste sludge as maggot feed, which can provide economic benefits and reduce environmental pollution. The Krida Manik Waste Bank is expected to be a pioneer in managing and utilizing tofu mud to feed maggots which can later be used as animal feed. This study uses a qualitative descriptive method where data is extracted as much as possible to obtain information regarding program management. The results of the activity show that there is potential for managing IPAL sludge using maggots. With the abundant potential of mud, people can use it as a renewable resource. However, capacity development and ongoing assistance need to be carried out to get maximum results.